Akustische Uberlegungen zum Willehalm Wolframs von Eschenbach - Greenfield, John (2004)
In this article, after referring to results already achieved in regard to an earlier analysis of Wolfram's Parzival, the author discusses to the extent to which sound and the perception of sound play a structurally important role in Wolfram's war epic, Willehalm.